Approach to Clostridioides difficile diarrheal infection - Laura Cordes Lourenço; Connor Prosty; Angela Huttner; Todd C. Lee; Emily G. McDonald (CMI Communications)
Incidence and clinical relevance: Clostridioides difficile infection (CDI) is a major cause of healthcare-associated diarrhea, with significant morbidity and mortality. CDI predominantly affects adults, with community-acquired cases on the rise. Following the first episode of CDI, 15-25% of patients will develop a recurrence. Mortality associated with CDI can approach 13.5% among patients 80 years and older. Etiologies/differential diagnosis: The differential diagnosis for CDI includes infectious colitis, with various other types of infectious colitis (e.g., cytomegalovirus, Klebsiella oxytoca, Escherichia coli 0157:H7), as well as non-infectious etiologies (e.g., Behcet’s disease, collagenous colitis, inflammatory bowel disease [IBD], ischemic colitis). Recommended treatment options and durations: Most treatment guidelines currently recommend fidaxomicin or vancomycin for initial non-fulminant CDI for 10 days. Metronidazole should be reserved for settings where first-line agents are unavailable. Recurrent cases may necessitate pulse-tapered regimens, faecal microbiota transplant or other microbiome-directed therapy. For fulminant CDI, high-dose enteral or rectal vancomycin, sometimes with adjunctive intravenous metronidazole or, in some jurisdictions tigecycline could be considered. Conclusion: Despite the advances in diagnosis and treatment, there are still important evidence gaps surrounding prevention, testing strategies, and management. High-quality clinical trials are required to compare effectiveness and determine the optimal treatment choice and duration for first episodes, first relapses, and subsequent relapses, as well as the role of preventive microbiota-restoring therapies and other forms of primary and secondary prophylaxis.